Application of Mactor Analysis for Halal and Sustainable Tourism Development in Posong, Indonesia - Muh Syaiful Bakhri; Abdul Wahab Fahrub; Muchammad Iqbal Chailani; M. Abdul Munjid (International Journal of Travel, Hospitality and Events, 2026)
This study aims to analyze the role of stakeholders in the development of Posong Tourism Area as a halal and sustainable tourism destination. This research employs a qualitative approach using the MACTOR (Matrix of Alliances, Conflicts, Tactics, Objectives, and Recommendations) analysis to identify the level of influence and dependence among stakeholders. Data were collected through in-depth interviews with key actors involved in tourism development, including government institutions, tourism managers, tourism awareness groups (Pokdarwis), business actors, and local communities. The results show that the key stakeholders in the development of Posong Tourism as a halal and sustainable destination include the Department of Tourism and Culture, Posong tourism management, Tourism Awareness Group (Pokdarwis), village government, and MSMEs. These actors have high levels of influence and dependence, indicating their strategic role in determining the direction of tourism development. The findings highlight the importance of strengthening collaboration and coordination among stakeholders to support the effective implementation of halal and sustainable tourism. This study implies that stronger stakeholder synergy can enhance sustainable tourism development and contribute to strengthening the local economy.